Pheromone baited trap for the management of red palm weevil, Rhynchophours ferrugineus F. (Coleoptera:Curculionide) population in coconut plantation - Rajapakse, C.N.K.; Gunawardena, N.E.; Perea, K.F.G. (Coconut Research Institute. Lunuwila, 1998)
4-methyl-5-nonanol (ferrugineol), the major component of the aggregation pheromone of rhynchophorus ferrugineus F. was evaluated as a lure for trapping of this pest in coconut plantations in Sri Lanka. Trap design, longevity of ferrugineol in field conditions, and the effect of trapping on damage incidence of R.ferrugineus were studied. N-pentanol, a known compound present in coconut stem volatiles was used in combination of ferrugineol in all tested traps. Trap designs tested were; an open plastic bucket, a funnel trap, and a modified metal trap. The open plastic bucket (5L) baited with ferrugineol -pentanol, which was hung on coconut palm stem at 1.5m, caught significatly more number of adult weevils than ferrugineol pentanol baited funnel and metal traps. An open plastic bucket trap was six times less expensive than the metal trap currently recommended by the Coconut Research Institute, Sri Lanka. Ferrugineol remained effective as a balt for 12 weeks under field conditions. High capture rates of adult R. ferrugineus were obtained in ferrugineol baited open bucket traps in plantations where the initial damage incidence was high. Monthly surveys of individual palms during pheromone trapping revealed that a sharp reduction of the number of coconut palms demaged by R. ferrugineus in 10 hectare experimental blocks. Continuous trapping of weevils with ferrugineol over a period of time significantly lowered the infestation of this pest.
Keywords: Agriculture; Pest control; Coconut plantation; Red palm weevil; Rhynchophorus ferrugineus F.; Pheromone baited trap; Ferrugineol